Pengembangan Multimedia Interaktif pada Materi Hidrolisis dalam Model Discovery Learning - Ulfah, Nurlaili Dwi; Sugiarti, Sugiarti; Salempa, Pince (Program Pasca Sarjana UNM, 2021)
This type of Research & Development research aims to develop and produce interactive multimedia (MMI) on hydrolysis materials in a valid, practical and effective discovery learning model. Adapting the ADDIE model, the analysis pays attention to curriculum aspects, student characteristics, and media needs. The design is carried out based on analysis by making an outline of the media content, learning descriptions, lesson plans and LKPD. The development stage consists of pre-production where multimedia flowcharts and media scripts are produced, production where MMI prototypes are produced, and post-production for reviewing MMI before use. The implementation is carried out on students of class XI SMAN 1 Simboro even semester year 2020/2021. Formative evaluation with a validation process on all devices, including research instruments, namely learning implementation sheets, teacher and student response questionnaires, and learning outcomes tests. The results showed that all devices met the very valid criteria with a score of 3.58 and 89.58% very feasible. MMI is valid with a score of 3.12 and 78.08% is feasible. Learning is carried out entirely with a score of 1.80 based on discovery learning syntax and 89.93% is very practical. For the teacher's response, a score of 3.39 was obtained with practical criteria and the student response with a score of 3.55 met the practical criteria. The percentage of class completeness, based on the results of the learning test, reached 86.67% which was very effective. This shows that the developed MMI meets the specified validity, practicality and effectiveness qualities.